PENGEMBANGAN GIM EDUKASI BERBASIS ANDROID UNTUK PENGENALAN BANGUN DATAR - Olief Ilmandira Ratu Farisi; Fitriyah, Siti; Sari, Alfi Alufiana; Akmalia, Latiful (TRANSFORMASI, 2023)
Two-dimensional shapes are one of the mathematical materials studied in grade1 of elementary school. This material requires spatial abilities. However, students still often have difficulty with this material, especially when determining the types. One solution to make it easier for students to understand two-dimensional shapematerial is to use android-based educational game learning media, so that students can learn while playing anywhere and anytime independently. The development is carried out using the Hannafin and Peck model, which consists of needs analysis, design, as well as development and implementation. The validation test was carried out by two material experts with results of 90.6% and one media expert with results of 87.5%. The trial was carried out on 21 users and obtained results of 97.5%. The results of validation tests and trials show that educational game media is very feasible and very effective for use in learning to recognize two-dimensional shapes. The development of mathematics educational games can be carried out at various levels of education and on various materials.